The Effect of Problem Based Learning Based on Hybrid Learning on Problem Solving in Mathematics Subjects at Islamic School: Pengaruh Problem Based Learning Berbasis Hybrid Learning terhadap Pemecahan Masalah pada Mata Pelajaran Matematika di Sekolah Islam - Arifia, Gadis; Nurdyansyah (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study is to analyze the effect and how much influence PBL (Problem Based Learning) based on hybrid learning has on solving mathematical problems at MI Al-Islam Plumpang. The research method used is quantitative research. Quantitative research is a research method that tests certain theories by examining the relationship between variables which are usually measured by research instruments so that they can produce data in the form of numbers (Creswell, 2012:5). In addition, data collection techniques using questionnaires (questionnaires), tests, and documentation. While the data analysis used is the normality test, validity test, reliability test, and T test (partial). Based on the data obtained from the results of the validation test, reliability test, and normality test, and the t-test, it can be concluded that the significance value of the experimental group is 0.531. So that 0.531 > 0.05, the problem-based learning model based on hybrid learning on problem solving in mathematics has a significant effect on students' understanding of mathematics in class 4 MI AL-Islam.